1980
DOI: 10.1099/00221287-119-2-517
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Properties of the Cell Envelope Components of Vibrio cholerae

Abstract: Several immunobiological properties of cell envelope components of Vibrio cholerae such as mitogenicity, antigenicity, adjuvanticity and toxicity were tested in mice. Killed whole bacteria, spheroplasts, lipopolysaccharide and outer membrane proteins possessed mitogenic activity as determined by [3H]thymidine uptake in spleen cell cultures. All these components predominantly stimulated murine bone-marrow derived (B) lymphocytes. The mitogenicity induced by V. cholerae lipopolysaccharide was similar in magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In the present study, proliferation of the mouse splenic lymphocytes was found to depend upon the concentration of stimulating antigen. These results are consistent with those of Lewis et al [37], who investigated the proliferative response of peripheral blood mononuclear cells (PBMCs) obtained from CT-B immunised subjects to CT-B, and Kabir and Mann [38], who studied the proliferation of murine splenic lymphocytes on stimulation with LPS or OMP of V. cholerae. The low SI and cpm values of proliferative responses recorded in the present study probably re¯ect the fact that oral administration of V. cholerae O139 strain MO45 induced only relatively small numbers of antigenspeci®c T-or B-cell precursors in the circulation.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, proliferation of the mouse splenic lymphocytes was found to depend upon the concentration of stimulating antigen. These results are consistent with those of Lewis et al [37], who investigated the proliferative response of peripheral blood mononuclear cells (PBMCs) obtained from CT-B immunised subjects to CT-B, and Kabir and Mann [38], who studied the proliferation of murine splenic lymphocytes on stimulation with LPS or OMP of V. cholerae. The low SI and cpm values of proliferative responses recorded in the present study probably re¯ect the fact that oral administration of V. cholerae O139 strain MO45 induced only relatively small numbers of antigenspeci®c T-or B-cell precursors in the circulation.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, extracted proteins had polypeptides similar to those of the outer membrane of V . cholerae isolated from the cell envelope by Triton X-100 (Kabir, 1980). Although the present method produced a few more polypeptides a major component in both the preparations had a molecular weight of 48000.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the electrophoretic profile of V. cholerae outer membrane proteins in polyacrylamide gels is distinct from those of other gram-negative organisms. These studies and others (16,17,34) indicate that the outer membrane of V. cholerae is a complex structure containing many proteins.Proteins exposed on the bacterial surface are likely to contribute to colonization of the host, and improved knowledge of the surface proteins should further our understanding of their role in colonization. The surface proteins of several bacterial species have been identified by iodination with membrane-impermeable enzymes (15,20,29,31) or the water-insoluble reagent, 1,3,4,6-tetrachloro-3,6-diphenylglycouril (Iodogen) (33).…”
mentioning
confidence: 70%